PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP MINAT BELI ULANG KONSUMEN KOREAN FOOD YEOBO TOPOKKI CABANG GRESIK - Kahyangan Ilmy Setya Budy; Sujani Sujani (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze the effect of product quality, service quality and price on consumers' repurchase intention of Korean food Yeobo Topokki. Data analysis was carried out using statistical assistance with the SPSS 21 program. The results of the analysis based on the t test showed that partially the product quality and service quality variables had a significant effect on consumer repurchase intention of Korean Food Yeobo Topokki Gresik Branch. Meanwhile, the price variable has a significant negative effect on consumer repurchase interest of Korean Food Yeobo Topokki Gresik Branch. Based on the F test, it is known that simultaneously the variables of product quality, service quality and price have a significant effect on consumer repurchase intention of Korean Food Yeobo Topokki Gresik Branch. Thus, it is hoped that the managers of the Korean Food Yeobo Topokki Gresik Branch will continue to maintain product quality, service quality and price, so that they can influence consumer repurchase intentions.